Pengaruh Variasi Media Carburizer terhadap Struktur Micro dan Kekerasan Baja Aisi 1045 - bunganaen, wenseslaus; Adoe, Dominggus G. H.; Pady, Aldy (Universitas Nusa Cendana, 2023)
The purpose of this study was to determine the effect of media variations of 90% kusambi charcoal and 10% shellfish, 90% kusambi charcoal and 10% rice husks, and 90% rice husks and 10% shells. Kusambi charcoal 90% and 10% rice husk, 90% rice husk and 10% shellfish. For the microstructure and hardness of steel AISI 1045, the material used in this research is medium carbon steel, the process of making the specimen is done by cutting it into several parts. The cutting is done to make it easier to place the specimens in the carburizing box then 90% kusambi charcoal mixed with 10% shellfish, 90% kusambi charcoal mixed with 10% rice husks, and 90% rice husks mixed with 10% clamshells. The specimens were subjected to a Carburizing treatment at a temperature of 9500C then a Rockwell hardness test and microstructure testing were carried out. From this study, it can be concluded that the highest average hardness value in the mixture of 90% Kusambi charcoal Carburizer and 10% shellfish was obtained at 39.25 HRC and the material hardness without treatment was 17.08 HRC. From the observation of the microstructure, the surface hardening occurs due to carbon diffusion into medium carbon steel